Hope and Future Orientation: A Phenomenological Study of Vocational High School Students’ Psychological Dynamics in Yogyakarta - Hadi Alhail; Kartika Nur Fathiyah; Adek Cerah Kurnia Azis; Sanita Carolina Sasea; Akram Musthafa; Siti Khofifatul Mardhiyyah; Izzunnazel Achmad Barqiallah; Rangga Octava Raisyabilla; Muhammad Ihsanul Fikri; Muhammad Ridwan (LPPM Universitas Pendidikan Mandalika, 2026)
This study aims to describe the psychological dynamics of vocational high school (SMK) students in constructing hope and future orientation. A qualitative approach with a phenomenological design was employed to explore the lived experiences of students conducted in a vocational high school setting in Yogyakarta City, Indonesia. Data were collected through in-depth interviews with eleventh-grade students and limited participatory observation, and were analyzed using Interpretative Phenomenological Analysis (IPA). The findings indicate that students’ hope is not understood as an abstract projection of the future, but rather as a concrete life goal oriented toward economic independence and readiness to assume adult roles. Students’ future orientation develops dynamically through processes of internal conflict, adaptation, self-acceptance, and the formation of alternative planning strategies. The results also reveal anxiety related to work readiness due to limited practical training and inadequate learning facilities. Nevertheless, students demonstrate psychological resilience by maintaining hope and engaging in adaptive efforts to face the future. This study recommends that policymakers evaluate the zoning system and improve practice facilities, and that educational counselors provide early career orientation services.